تطبيق المبادئ العلمية لتكوين محافظ الاستثمار في المصارف التجارية السورية ( دراسة مقارنة بين المصارف التجارية السورية العامة والخاصة) - محمد, رامي (Latakia University Journal - Economic and Legal Sciences Series, 2018)
يهدف البحث إلى تقييم مدى الالتزام بالمبادئ النظرية والعلمية في تكوين محافظ الاستثمار في المصارف التجارية السورية العامة والخاصة والمتمثلة في : مبدأ التنويع، مبدأ المبادلة بين العائد والمخاطرة، مبدأ السياسات المتبعة في تكوين المحفظة، مبدأ الملائمة، مبدأ ضمان رأس المال المستثمر وثبات العائد، وإجراء المقارنة بين هذه المصارف من حيث مدى التزامها بالمبادئ العلمية. ولتحقيق هذا الهدف قام الباحث بدراسة ميدانية على المصارف التجارية السورية العامة والخاصة والبالغ عددها (12) مصرف، من ناحية أخرى قام الباحث بتصميم استبانة مكونة من خمسة محاور يندرج تحتها المبادئ العلمية لتكوين محافظ الاستثمار، وباستخدام أسلوب المسح الشامل تم توزيع (203) استبانة على مجتمع البحث المكون من مديري المصارف ونوابهم ومساعديهم، والمديرين الماليين والتخطيط والتطوير والتسليف والحسابات والمخاطر، تم استرداد (165) استبانة صالحة للتحليل الإحصائي، وقد توصلت الدراسة إلى أن المصارف التجارية السورية العامة والخاصة قطعت شوطاً في تطبيق المبادئ العلمية لتكوين محافظ الاستثمار، إذ كان التزامها بتطبيق هذه المبادئ جمعيها وحدة واحدة عند المستوى المرتفع، وأشارت نتائج الدراسة إلى عدم وجود فروق ذات دلالة بين مستوى التزام المصارف التجارية العامة بالمبادئ العلمية لتكوين محافظ الاستثمار وبين مستوى التزام المصارف التجارية الخاصة بتلك المبادئ. The research aims to assess the extent of adherence to the theoretical and scientific principles in the formation of investment portfolios in Syrian commercial and public banks, namely: the principle of diversification, the principle of exchange between return and risk, the principle of policies in the composition of the portfolio, the principle of appropriateness, Compare these banks in terms of their commitment to scientific principles In order to achieve this objective, the researcher conducted a field study on the commercial and private commercial banks of (12) banks. On the other hand, the researcher designed a questionnaire consisting of five axes that cover the scientific principles for the formation of investment portfolios. The research community consisting of bank managers, their deputies and their assistants, financial managers, planning, development, credit, accounts and risks, was retrieved (165) valid questionnaire for statistical analysis. The study concluded that Syrian commercial public and private banks have made progress in applying the principles Mieh the composition of investment portfolios, as was its commitment to the application of these principles combine in a single unit at the high level, and the results indicated that there were no significant differences between the level of general commercial banks 'commitment to scientific principles for the formation of investment portfolios and the level of private commercial banks' commitment to those principles.